Chemical and functional properties of Some legumes available in the local market of Brack city (The International Journal for Scientific Research, 2025)
This study compared the chemical and functional properties of some legume seeds and their protein isolates. The results showed that Pea flour, Bean flour, and Cowpea flour contained 8.27-10.13% of moisture, Bean flour contained the highest ash percentage of 4.22% compared to Pea and Cowpea flour, while the Cowpea flour had the highest protein, crude fat and fibre levels of 32.20, 1.83 and 7.62%, respectively. The highest carbohydrate content was recorded for the bean flour (64.18%).  The Bean protein isolate contained the highest levels of moisture, ash, crude fat and fibre of 6.01, 2.06, 0.63 and 0.47%, respectively. Protein and carbohydrate were recorded for the Pea protein isolate of 91.54 and 7.85%, respectively. The results of the functional properties showed that the Bean flour had the highest water and oil binding capacity of 1.730 g flour/10 ml water and 1.223 g flour/10 ml oil, and the Pea flour had the highest emulsion binding capacity of 1.837 g flour/10 ml emulsion. For the protein isolate, the Pea protein isolate showed the highest water-binding capacity (3.11 g flour/ml water) and emulsion-binding capacity (4.063 g protein/10 ml emulsion), while the bean protein isolate had the highest fat-binding capacity (0.831 g protein/10 ml oil). The effect of the pH on some protein characteristics was observed. The foam ability increased by increasing the pH from 4 to 7, and the optimum foam ability was achieved at pH (7). The results also showed that the best foam stability was at pH (7). The Pea protein isolate achieved the highest foam ability and stability compared with the Bean and Cowpea protein isolates. The results also showed that the minimum concentration required to form a gel was 12% for the Pea protein isolate and 14% for the Bean and Cowpea protein isolates.
Keywords: Chemical Composition; Functional Properties; Beans; Peas; Cowpeas